Simplified method for analyzing inherent properties of large-scale liquid-filled pipelines - Shen, Zuming; Pang, Seng; Jiang, Zihang; Wu, Guohui (Frontiers in Earth Science, 2025)
In the current research investigation, a simplified method of analysis of the dynamic characteristics of liquid-filled pipeline systems in engineering applications has been developed. This method models several representative structural configurations of complex pipelines and incorporates a fluid-structure interaction formulation that accounts for the inertial effects of the internal fluid through a modified added mass representation. The approach demonstrates high accuracy and computational efficiency and has been validated through experimental results, supporting its use as a practical tool for rapid vibrational mode analysis in pipeline systems. Numerical simulations were carried out to determine the first 50 natural frequencies and modes of a water-supply pipeline in the pumping station. Resonance-prone frequencies were identified in the range of 154.1–173.4 Hz. Based on the findings, recommendations were proposed: namely, a change of excitation directions to reduce resonance risk, offering practically useful guidance for the mitigation of vibrations and noise in engineering projects. Further investigations carried out were with respect to vibration responses at critical pipeline locations under varying excitation frequencies. Analysis was conducted with respect to the maximum velocity of vibration and stress at stress-concentration points compared to the permissible limits as defined by relevant standards. In this way, these findings provide insight into structural optimization and vibration control methods for pipeline systems with extraordinary vibratory responses. Overall, the study provides a systematic approach towards a dynamic analysis, effective diagnostics, and active control of pipeline vibrations, aiming to enhance operational safety and reliability.